Ethnicity, social influence, eco-label and purchase intention of consumers of green home electronic products / Nor Hashima Hashim, Wan Kalthom Yahya and Siti Aisyah Asrul - Hashim, Nor Hashima; Yahya, Wan Kalthom; Asrul, Siti Aisyah (Penerbit UiTM (UiTM Press), 2018)
Today green consumers are creating a new economy around the globe. Indeed, the ‘green consumer’ idea was the focus of academicians and manufacturers at the end of 1980s and in the early 1990s. Likewise, rising knowledge on the various environmental problems has led a change in the way consumers go about their life. People are insistently trying to reduce their impact on the environment and living a ‘green lifestyle’. As a result, business has seen this change in consumer attitudes and is trying to sell many green products by exploiting the potential in the green market industry. Using green home electronic products are environmental initiatives for consumers to become green consumers. Research, although limited in the areas of ethnicity and green electronic home products, does suggest that a consumer’s ethnicity will influence their attitude toward home electronic choices, which in turn will affect their purchase decision. Therefore, the goal of the present study was to expand the body of research concerning ethnicity and its influence on purchase of green home electronic products. Therefore, this study examines if there exist differences in ethnic groups for the intention to purchase home electronic products, namely air conditioner, refrigerator and television. A total of 251 self-administered questionnaires were collected from respondents living within the cities of Klang Valley, Malacca and Penang. Results of the study show eco-label information is important in all three ethnic groups while social influence was not important to the Indians when purchasing green home electronic products. The results of the study indicate the importance of viewing ethnic consumer groups as unique markets and suggest some possible areas for further research.